(untitled) (Journal of Nobel Medical College, 2021)
The clinical picture of infective endocarditis varies from the asymptomatic stage for a long duration to an acute fulminant course. A high index of suspicion is necessary whenever a patient presents with nonspecific symptoms and some peripheral clinical signs with a cardiac murmur. We report a case of sub-acute IE involving multiple left and right side cardiac valves with underlying rheumatic heart disease (RHD).